First languages and las technologies for education - Julio VERA VILA (Ediciones Universidad de Salamanca, 2013)
This article is a reflection on how each human being's learning process and the cultural development of our species are connected to the possibility of translating reality -what we think, what we feel, our interaction- a system of signs that, having shared meanings, enrich our intrapersonal and interpersonal communication. Spoken language was the first technology but being well prepared genetically for it, we learn it through immersion; the rest of them, from written language to hypermedia, have to be well taught and even better learned. We conclude by highlighting the necessity of taking advantage of the benefits provided by the new technologies available nowadays in order to overcome the digital divide, without forgetting others such as literacy acquisition, which are the base of new technologies. Therefore we need a theory and practice of education which comprises its complexity and avoids simplistic reductionism.